The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5507/pol.2016.007
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of items of the Braden scale, the Norton scale and Waterlow scale

Abstract: 1Ústav ošetřovatelství a porodní asistence, Lékařská fakulta, Ostravská Univerzita v Ostravě, Česká republika 2 Ústav ošetrovateľstva, Jesseniova lekárska fakulta v Martine, Univerzita Komenského v Bratislave, Slovenská republika ABSTRAKT Východiská: V súčasnosti existuje na svete takmer 40 škál na posúdenie rizika vzniku dekubitu. Napriek ich množstvu boli psychometrické vlastnosti testované len u niektorých. Cieľ: Zistiť stupeň inter-rater reliability jednotlivých položiek vybraných škál na posúdenie rizika … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…With low inter-rater reliability values, one general nurse may indicate the patient as at high risk while the second nurse may assign the patient to the no risk group. In the psychometric testing the inter-rater reliability KontAKt / Journal of nursing and social sciences related to health and illness n u r s I n g Ševčíková et al / KONTAKT 21 of the total measuring instrument score, as well as their individual items, may be evaluated (Šáteková and Žiaková, 2016;Urbánek et al, 2011). Foreign research studies have demonstrated the inter-rater reliability values for Nu-DESC to be κ = 0.47 -0.83 (κ, ICC).…”
Section: Introductionmentioning
confidence: 99%
“…With low inter-rater reliability values, one general nurse may indicate the patient as at high risk while the second nurse may assign the patient to the no risk group. In the psychometric testing the inter-rater reliability KontAKt / Journal of nursing and social sciences related to health and illness n u r s I n g Ševčíková et al / KONTAKT 21 of the total measuring instrument score, as well as their individual items, may be evaluated (Šáteková and Žiaková, 2016;Urbánek et al, 2011). Foreign research studies have demonstrated the inter-rater reliability values for Nu-DESC to be κ = 0.47 -0.83 (κ, ICC).…”
Section: Introductionmentioning
confidence: 99%